Integral Modeling for Deviation Correction Trajectory of the Mechanical Vertical Drilling System - Lin Chai; Kai Zhang; Dengwen Yang; Baolin Liu; Delong Zhang (Machines, 2021)
The deviation correction trajectory of the mechanical vertical drilling system (MVDS) is very important because it is the final embodiment of performance. However, it is impossible to obtain it at the design stage, except when using simulation methods. In this paper, tool face angle model and other theoretical models were established, respectively, and the trajectory simulation method was created through model coupling. Next, the method was used to simulate the trajectory of MVDS under two typical working conditions. The results indicate that the critical deviation angle is the deviation control accuracy of the MVDS. The existence of critical deflection angle makes MVDS correct deviation and change azimuth at the same time, resulting in the trajectory being a three-dimensional curve, which has the tendency of drifting to the left. Furthermore, the deviation and azimuth change rate are constantly changing in the process of drilling. The results also show that the MVDS is unable to correct the horizontal displacement of the downhole. The proposed method and analysis results are helpful to find out and solve the problem of the current design as soon as possible, and to provide guidance for the subsequent structure optimization.